Difficulties in diagnosing and predicting possible complications in patients after heart transplantation: single-center experience in the Krasnodar region - L. K. Tkhat; Z. G. Tatarintseva; E. D. Kosmacheva (Российский кардиологический журнал)
Aim. To evaluate the early and long-term outcomes of heart transplantation (HT) at the Research Institute of the S. V. Ochapovsky Regional Clinical Hospital № 1.Material and methods. On the basis of the Research Institute of the S. V. Ochapovsky Regional Clinical Hospital № 1 from March 2010 to March 2023, 230 HTs were carried out. Among the patients, men predominated 86% (n=198), women — 14% (n=32). The mean age was 48,3±11,7 years. The reason for HT in 42,6% (n=98) was ischemic cardiomyopathy (ICM), in 40% (n=92) — dilated cardiomyopathy (DCM), while 17,4% were operated on for another cardiac pathology (n=40). All recipients underwent immunological examination, endomyocardial biopsy (EMB), 2D-speckle-tracking echocardiography (2D-STE), transthoracic echocardiography (TTE), coronary angiography (CAG), as well as a number of studies for early diagnosis of possible cancer complications.Results. Acute rejection during the first three years was detected in 77 recipients (42,5%), of which cellular rejection (grade ≥2, 3) and humoral rejection was verified in 49 and 28 recipients, respectively. During the entire follow-up period, de novo anti-human leukocyte antigen (HLA) antibodies were detected in 34 recipients in the posttransplantation period, of which 50% (n=17) and 35% (n=12) were diagnosed with humoral and cellular rejection, respectively. Of the 34 patients with anti-HLA antibodies, 11 (32%) died. All of them died due to a humoral rejection. The survival rate of patients with antibodies was lower (59%) than in patients without antibodies (66%), p=0,023. The annual survival rate of all patients after transplantation in our center was 83,1% (during the first year after transplantation, 30 and 9 patients died due to an acute rejection and infectious complications, respectively).Conclusion. Since the introduction and modification of immunosuppressive therapy regimens, tremendous progress has occurred, and the incidence of acute cellular rejection has decreased. However, the risk of humoral rejection and long-term complications remains one of the main reasons for graft failure.